Nothofagus pumilio regeneration failure following wildfire in the sub-Antarctic forests of Tierra del Fuego, Argentina - Ruggirello, Matthew; Bustamante, Gimena Noemi; Soler Esteban, Rosina Matilde (Forestry: An International Journal of Forest Research)
Wildfires on the island of Tierra del Fuego in southern Argentina are not considered to have been a historic driver of forest dynamics. However, dramatic increases in the human population of the island over the last half-century have greatly increased fire ignition sources and thus the frequency of wildfires in the region. Lenga (Nothofagus pumilio (Poep. et Endl.) Krasser) forests support diverse ecosystem services by providing habitat for endemic f lora and fauna and also represent a valuable timber resource for the forest industry of Tierra del Fuego. Evaluating the impact of forest fires on lenga regeneration is important not only because lenga is a native, slow-growing species that seems to lack adaptations that would allow it to recover rapidly after fire, but also because low tree species diversity on the island of Tierra del Fuego means lenga post-fire regeneration failure may lead to ecosystem state shifts. To determine how site characteristics and fire-impacted variables modulate post-fire regeneration densities and spatial patterns in lenga forests, we installed 192 plots (160 burned, 32 unburned) in which we measured site-characteristic (e.g. aspect, elevation) and fire-impacted (e.g. basal area, canopy cover) variables and tallied seedlings and saplings. Regeneration densities were significantly lower in burned than unburned plots. This was exacerbated with increasing distance from the unburned forest edge. Increasing distance to live trees that either survived fire or were outside the burned area negatively impacted regeneration as well. Time since fire negatively affected sapling, but not seedling counts. We concluded that lenga regeneration in the interior of burned areas is largely absent, delaying and potentially preventing forest recovery. These interior areas of burned lenga forests are unlikely to regenerate closed-canopy tree cover through passive restoration alone. Active restoration may be needed in these critical areas where live legacy trees are not present. Fil: Ruggirello, Matthew. ...